a/
\(\frac{a}{b}=\frac{c}{d}\Rightarrow\frac{2a}{3b}=\frac{2c}{3d}\Rightarrow\frac{2a}{2c}=\frac{3b}{3d}=\frac{2a+3b}{2c+3d}=\frac{2a-3b}{2c-3d}\)
\(\Rightarrow\frac{2a+3b}{2a-3b}=\frac{2c+3d}{2c-3d}\left(dpcm\right)\)
b/
\(\frac{a}{b}=\frac{c}{d}\Rightarrow\frac{a^2}{ab}=\frac{c^2}{cd}\Rightarrow\frac{a^2}{c^2}=\frac{ab}{cd}\left(1\right)\)
\(\frac{a}{b}=\frac{c}{d}\Rightarrow\frac{ab}{b^2}=\frac{cd}{d^2}\Rightarrow\frac{b^2}{d^2}=\frac{ab}{cd}\left(2\right)\)
Từ (1) và (2) \(\Rightarrow\frac{ab}{cd}=\frac{a^2}{c^2}=\frac{b^2}{d^2}=\frac{a^2-b^2}{c^2-d^2}\left(dpcm\right)\)